Perkembangan Pendidikan di Era 5.0 - Sukatin; Siti Ariska Nur Hasanah; Oktavia Ningsi; Retno Intan Pratiwi; Warjad Subagia (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
The development of science and technology is now increasingly showing rapid progress. Until now humans have arrived at the era of society 5.0 which is marked by the increasingly centralized role of technology in human life. The industrial era changed the way of teaching and learning in a lesson. The learning method is not only through the lecture method, now teachers need to reformulate learning methods that utilize technology while still emphasizing the human resource aspect, namely so that humans can anticipate the consequences of the emergence of the 4.0 industrial revolution era. The purpose of this research is to look at the development and role of education in the 5.0 era. The method in this study is to use a library research method or approach. The results in the Era research that must be watched out for from now on is the era of society 5.0. Education in Indonesia in welcoming this era is by first looking at existing infrastructure in Indonesia, developing human resources, synchronizing education and industry and using technology as a tool for teaching and learning activities. There are four things that make educational institutions produce quality graduates, namely competency-based education, the use of IoT (Internet of Things), the use of virtual or augmented reality and finally the use of AI (Artificial Intelligence).